Pengamanan Tebing Pantai Tanjung Playu Batam - Nur Yuwono; Muhammad Effendi Saputra; Y Yuwono (Faculty of Engineering, Universitas Gadjah Mada, 2003)
Tanjung Playu Beach, Batam Island, is a wonderfull fishermen village. The housing and public facilities are built a long the coast. These buildings and facilities are subject to wave attack, especially during wave season and high tides. In order to combat this problem, a special research is carried out.This research is intended to analyze the problem and to find out the solution through the hydraulic model test. Based on this research, the design of sea wall is carried out in order to gct a building which environmentalyfriendly.Keywords: wave attack, hydraulic model test, sea wall.